Primary prevention of stroke: randomised controlled pilot trial protocol on engaging everyday activities promoting health. Issue 11 (2nd November 2019) - Patomella, Ann-Helen; Guidetti, Susanne; Mälstam, Emelie; Eriksson, Christina; Bergström, Aileen; Åkesson, Elisabet; Kottorp, Anders; Asaba, Eric
Abstract : Introduction: Stroke is a globally common disease that has detrimental effects on the individual and, more broadly, on society. Lifestyle change can contribute to reducing risk factors for stroke. Although a healthy lifestyle has direct benefits, sustaining and incorporating healthy activities into everyday life is a challenge. Engaging everyday activities have the potential to support lifestyle change and to promote sustainable activity patterns. Current healthcare is failing to reduce modifiable risk factors in people at risk, and in addition to current practice, there is a need for systematic and efficient non-pharmacological and non-surgical stroke-prevention strategies. The aim of the pilot study was to increase knowledge about the effects of a prevention programme and its feasibility to promote sustainable and healthy activity patterns among persons at risk of stroke. Methods and analysis: The proposed pilot study will be a two-armed randomised, assessor-blinded, parallel pilot trial. The study will include feasibility data, investigating acceptability and delivery of the intervention. Persons at risk of stroke (n=60) will be included in a mobile phone-supported prevention programme. The 10-week programme will be conducted at primary healthcare clinics, combining group meetings and online resources to support self-management of lifestyle change. Main outcomes are stroke risk, lifestyle habits and healthy activity patterns. Assessments will be performed at baseline and at follow-up (immediately following the end of the programme and at 6 and 12 months). Effects of the programme will be analysed using inferential statistics. Feasibility will be analysed using both qualitative and quantitative methods. Ethics and dissemination: The study has been approved by the Regional Ethical Review Board in Stockholm, Sweden, being granted reference numbers 2015/834-31, 2016/2203-32 and 2019/01444. Study results will be disseminated through peer-review journals and presentations to mixed audiences at regional and international conferences. Trial registration number: NCT03730701 .